Edukasi Daring Mengembangkan Keseimbangan Kerja-Keluarga di Masa Pandemi - Sri Lestari; Gita Aulia Nurani; Wisnu Sri Hertinjung; Yasrin Nur Fajriyati; Aris Purwanto; Day Sabilla Widya Ar-ra Uufu (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Nowadays, organizations have had concerned about term work-family balance. It is related to employee welfare and performance at work. During the Covid-19 pandemic, the work system changed rapidly. There has been a radical change from working in the office to working from home. Based on research results, the pandemic causes problems in work-family balance. Even though achieving balance in work and family matters is essential to maintain mental health during this pandemic. Therefore, it is necessary to conduct online socialization and education regarding ways to achieve work-family balance during this pandemic. This community service activity aims to increase participants' knowledge about ways to achieve a balance of family work. The action was carried out in a webinar with a material presentation by the resource persons and discussion. The target of this activity is the general public. Data was collected through questionnaires and question-and-answer sessions. Based on the data, it was found that webinar participants gained additional knowledge about managing tasks in the workplace and family. This knowledge can be applied by individuals who have worked and become the provision of not yet married participants.